Analysis of risk factors of recurring non-specific low back pain with particular emphasis on “new” predictive factors - Citko, Anna; Górski, Stanisław; Marcinowicz, Ludmiła; Górska, Anna (Family Medicine & Primary Care Review, 2017)
Background. Non-specific low back pain (NSLBP) is one of the most frequent causes of medical consultations. The recurrence rate is high and estimated to be within the range from 25% to 70% in different populations. Currently, the contribution of various predictive factors of NSLBP is being discussed. What seems to be interesting are studies on the impact of chronic diseases on the occurrence of NSLBP. Objectives . The purpose of this paper is to assess the frequency and analyse the risk factors of recurring NSLBP with a particular emphasis on “new” predictive factors. Material and methods . 609 people (medical staff) aged 30–55 participated in the study. The study was conducted by means of a random employee survey supervised by the authors of this paper. Results . 253 subjects (41.54%) complained of recurring NSLBP. Recurrences of NSLBP occurred in 48.34% of the respondents aged between 30 and 40. In the multivariate logistic regression, the following factors had, inter alia, a significant influence on the occurrence of recurring NSLBP: excessive coffee consumption (≥ 6 cups a day), smoking, hyperlipidemia, occurrence of low back pain in the respondent’s family (p < 0.001; p < 0.001; p < 0.01; p < 0.01, respectively). Conclusions . 1. Prevention measures aimed at prevention of NSLBP recurrences should include young adults. 2. An important element in the diagnostic and therapeutic process is a holistic approach of the family doctor to a patient with recurring NSLBP, taking into account not only the nature of the professional work connected with biomechanical load on the spine, but also the patient’s lifestyle and their concurrent diseases. 3. It is necessary to conduct further research on the impact of chronic diseases on the occurrence of recurring NSLBP. Evidence showing the existence of new predictive factors may be a basis for the implementation of better prevention strategies aimed at the prevention of NSLBP recurrence.